Differential diagnostic value of plain CT scan in adrenal adenoma and non-adenoma: A two-center control study of mean attenuation value, minimum attenuation value, and CT histogram - Han, Zhijiang; Wu, Mengwei; Wei, Peiying; Zhu, Hanlin; Zhang, Xiaohan; Ding, Zhongxiang; Zhang, Ming (Frontiers in Endocrinology, 2022)
Objectives: To investigate the value of mean attenuation value (AVmean), minimum attenuation value (AVmin), and CT histogram (CTH) for the differential diagnosis of adrenal adenoma and non-adenoma in two medical centers. Methods: The plain CT data of 403 cases of adrenal adenoma and 141 cases of non-adenoma in center A were retrospectively analyzed, and compared with data of 86 cases of adenoma and 71 cases of non-adenoma in center B. All cases were confirmed by pathology or clinical follow-up. The diagnostic efficacy of AVmean ≤ 10 Hounsfield units (HU), AVmin ≤ 0 HU, and CTH negative pixels ≥ 10% for adrenal adenoma was compared between the two medical centers. Results: In medical centers A and B, the AUC of AVmean for the differential diagnosis of adenoma and non-adenoma was 0.956 and 0.956, respectively, and the corresponding sensitivity, specificity, and accuracy were, 0.591 and 0.663, 1.000 and 1.000, 0.697, and 0.815, respectively, when the threshold was ≤ 10 HU. The AUC of AVmin was 0.941 and 0.958, respectively, and the corresponding sensitivity, specificity, and accuracy were 0.869 and 0.826, 0.986, and 0.972, 0.899, and 0.892, respectively, when the threshold was ≤ 0 HU. The AUC of CTH negative pixels was 0.948 and 0.952, respectively, and the corresponding sensitivity, specificity, and accuracy were 0.759 and 0.674, 1.000 and 1.000, 0.822, and 0.822, respectively, when the threshold was ≥ 10%. Conclusion: AVmean≤10 HU, AVmin≤0 HU, and CTH negative pixels ≥ 10% are all important parameters for differentiating adrenal adenoma from non-adenoma, and there was a high consistency between the two medical centers. Although the specificity of AVmin≤0 HU was slightly lower than that of AVmean≤10 HU and CTH negative pixels ≥10%, the sensitivity and accuracy were significantly higher than those of both, and combination of these three parameters could assist clinicians to develop personalized treatments.